Potential of hydrogen (pH) differentially modulates cadmium stress response in abscisic acid-deficient sitiens tomato mutant - Pompeu, Georgia Bertoni; Ambrosano, Guilherme Bovi; Vilhena, Milca Bartz; Carvalho, Rogério Falleiros; Gratão, Priscila Lupino; Andrino, Felipe; Lira, Simone Possedente De; Azevedo, Ricardo Antunes (Instituto Agronômico de Campinas, 2019)
ABSTRACT Uptake of nutrients and cadmium (Cd) are dependent upon many factors, including plant species, ions concentration and pH. Tolerance to Cd-induced oxidative stress can be modulated by phytohormones such as abscisic acid (ABA), which induce the production of reactive oxygen species, activating proteins and enzymes involved in stress response and possibly stress tolerance. The present study aimed to evaluate the biochemical variations induced by Cd in ABA-deficient sitiens tomato mutant (sit) and its wild-type counterpart, Micro-Tom (MT), grown at different pH conditions. The plants were cultivated in nutrient solution (pH 5, 6 and 7; 20-days) and were then further grown over a 48-h period in 0 or 50 ?M CdCl2 at pH 6. Before Cd addition, the concentrations of nitrogen, sulfur, copper, iron and zinc were determined and variations in nutrients concentrations were observed. After Cd addition, sit roots grown at pH 5 and 7 did not exhibit differences in ascorbate peroxidase (APX) activity in 0 or 50 ?M CdCl2, and sit root grown at pH 6 exhibited lower glutathione reductase (GR) activity in the presence of Cd. Moreover, sit shoot grown at pH 5 showed decreased activities of superoxide dismutase (SOD), Mn-SOD II and Cu/Zn-SOD V, in 0 and 50 ?M CdCl2. The results indicated that pH modulates the plant nutrition in a complex way and may involve multiple ABA signaling pathways. Likewise, ABA status seems to be related with the Cd-translocation within the plant, suggesting that Cd, ABA and pH responses cannot be evaluated as isolated systems.
Keywords: antioxidant enzymes; Micro-Tom; mineral nutrition; oxidative stress; Solanum lycopersicum